Imam Al-Haramayn al-Juwayni on the symbiosis between theology and legal theory - Wan Azhar Wan Ahmad (Islamic and Strategic Institute Berhad, 2017)
Beginning from the early 5th A.H./11th C.E. century, Muslim scholars writing on legal theory (uṣūl al-fiqh) was more increasingly inclined to incorporate in their works discussion of issues that do not strictly belong to the legal domain only but rather to the theological and philosophical spheres as well. No adequate explanation was given on why and how this took place in Islamic intellectual history. Focusing on the legal works of Imām al-Ḥaramayn al-Juwaynī (d. 478/1085), this study attempts to deliberate on the matter. It undertakes to show that in Islamic academic tradition, there exists a mutually advantageous and symbiotic interaction between theology ('ilm al-kalām) and legal theory ('ilm uṣūl al-fiqh). This book examines the organic symbiosis between the two disciplines with a cluster of theological issues that have been frequently incorporated in the literature of Islamic legal theory.